Alessandro Bausi, Gianni Dore and Irma Taddia: Materiale antropologico e storico sul “rim” in Etiopia ed Eritrea. Anthropological and Historical Documents on «Rim» in Ethiopia and Eritrea - Gebremedhin, Ezra (Aethiopica, 2003)
Review